Applying ISO 9000 quality management systems (ITC UNCTAD/WTO GenevaCH, 1996)
Deals with basic concepts of quality control and quality management. Explains the structure and content of the ISO 9000 standards. Discusses the establishment, implementation, auditing and third-party certification of quality management systems, as relevant to small and medium-sized enterprises.
Bibliography: p. 139